Emotion regulation: exploring the impact of stress and sex - Kinner, Valerie L.; Het, Serkan; Wolf, Oliver T. (Frontiers in Behavioral Neuroscience, 2014)
Emotion regulation is a major prerequisite for adaptive behavior. The capacity to regulate emotions is particularly important during and after the encounter of a stressor. However the impact of acute stress and its associated neuroendocrine alterations on emotion regulation have received little attention so far. This study aimed to explore how stress-induced cortisol increases affect three different emotion regulation strategies. 72 healthy men and women were either exposed to a stressor or a control condition. Subsequently participants viewed positive and negative images and were asked to up- or down-regulate their emotional responses or simultaneously required to solve an arithmetic task (distraction). The factors stress, sex and strategy were operationalized as between group factors (n = 6 per cell). Stress caused an increase in blood pressure and higher subjective stress ratings. An increase in cortisol was observed in male participants only. In contrast to controls, stressed participants were less effective in distracting themselves from the emotional pictures. The results further suggest that in women stress enhances the ability to decrease negative emotions. These findings characterize the impact of stress and sex on emotion regulation and provide initial evidence that these factors may interact.